(untitled) (International Journal of Nursing Education, 2026)
Accreditation plays a critical role in ensuring the quality, credibility, and continuous improvement of nursing education programs worldwide. This article examines the role of accreditation in nursing education, with an emphasis on quality assurance, public trust, and the promotion of ongoing program evaluation and enhancement. Particular attention is given to the benefits of international nursing accreditation for students, faculty, institutions, employers, and communities of interest, including improved educational quality, enhanced global recognition, and increased mobility of graduates. The article also addresses challenges associated with international accreditation, such as time, financial costs, and the sustained commitment required to maintain compliance with accreditation standards. Additionally, the work highlights international accreditation efforts led by the Accreditation Commission for Education in Nursing (ACEN), outlining its global reach, comprehensive Standards and Criteria, and support for programs seeking this recognition. The article also provides an overview of the ACEN Standards and Criteria as applied in international contexts, illustrating how global quality benchmarks are implemented while respecting local regulatory and cultural frameworks.By applying consistent, globally relevant standards while allowing programs to reflect local regulatory and cultural contexts, international accreditation supports excellence in nursing education and contributes to the preparation of competent, ethical, and practice-ready nurses worldwide.